1993
DOI: 10.1901/jeab.1993.59-333
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Discrimination and Equivalence Relations: Control by Negative Stimuli

Abstract: Three adult subjects were taught the following two-sample, two-comparison conditional discriminations (each sample is shown with its positive and negative comparison, in that order): A1-B1B2, A2-B2B1; B1-C1C2, B2-C2C1; and C1-D1D2, C2-D2D1. A teaching procedure was designed to encourage control by negative comparisons. Subjects were then tested for emergent performances that would indicate whether the baseline conditional discriminations were reflexive, symmetric, and transitive. The tests documented the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
1
34

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 19 publications
(18 reference statements)
9
122
1
34
Order By: Relevance
“…Since, in the present study, participants who showed complete sample-S+ control also tended to show complete sample-S-control, it is difficult to determine whether sample-S-control was necessary or not for class formation. this could be done with a method that induced particular controlling relations (e.g., Johnson & Sidman, 1993), so that equivalence outcomes could be compared for participants who learned only sample-S+ relations and participants who learned both sample-S+ and sample-S-relations.…”
Section: Stimulus Control Relationsmentioning
confidence: 99%
“…Since, in the present study, participants who showed complete sample-S+ control also tended to show complete sample-S-control, it is difficult to determine whether sample-S-control was necessary or not for class formation. this could be done with a method that induced particular controlling relations (e.g., Johnson & Sidman, 1993), so that equivalence outcomes could be compared for participants who learned only sample-S+ relations and participants who learned both sample-S+ and sample-S-relations.…”
Section: Stimulus Control Relationsmentioning
confidence: 99%
“…Until recently, nearly all equivalence research showing such differences was conducted with two-choice MTS methods (Fields, Hobbie-Reeve, Adams, & Reeve, 1999; K. J. Saunders et aI., 1993; R. R. Saunders, Drake, & Spradlin, 1999; R. R. Saunders et aI., 1988;Spradlin & Saunders, 1986). Several researchers have noted that with two-choice MTS procedures, responding during training and testing might induce sample/S-control rather than sample/S+ control (Carrigan & Sidman, 1992;Johnson & Sidman, 1993;Sidman, 1994). Sample/S-control refers to the inference that "correct" responding is a function of "rejecting" the incorrect choice stimulus in the trial as opposed to "selecting" the correct choice (Carrigan & Sidman, 1992).…”
Section: Almentioning
confidence: 99%
“…The training and testing format used prior to the set-merger tests of Phase 4.3 always employed configurations of two comparison stimuli from the S-class with one from the S+ class (e.g., if the correct comparison was a stimulus from Set 1, the incorrect comparisons were both from Set 2). Under such conditions, subjects can form an exclusion-based response strategy that focuses on the relationship between the sample and the incorrect comparison(s) rather than the relationship between the sample and correct comparison (Carrigan & Sidman, 1992;Johnson & Sidman, 1993). In the current study, such a response strategy could have produced accurate performances during training and during the equivalence tests of Phases 2.5 and 3.5.…”
Section: Do the Results Qualify As Stimulus Equivalence?mentioning
confidence: 99%